Effect of oral bacteria on peripheral blood leukocyte interleukin-6 and soluble interleukin-6 receptor production - Lindemann, R A; Kinder Haake, S A; Kjeldsen, M; Avanessian, A B (Oral microbiology and immunology, 1996)
To determine the effect of pathogenic oral bacteria on interleukin 6 (IL-6) and soluble IL-6 receptor production, we measured their release by human peripheral blood mononuclear cells in vitro. Unseparated peripheral blood mononuclear cells, peripheral blood lymphocytes (monocyte depleted), pure T cells, or monocytes were cultured with Actinobacillus actinomycetemcomitans, Capnocytophaga gingivalis, Capnocytophaga ochracea, Fusobacterium nucleatum or Porphyromonas gingivalis for 24 h. Supernatants were tested for IL-6 and soluble IL-6 receptor by enzyme-linked immunosorbent assay. Only monocytes and peripheral blood mononuclear cells responded with significant IL-6 release in the presence of all bacteria tested. However, peripheral blood lymphocytes were capable of producing IL-6 when activated by phytohemagglutinin or IL-2 followed by bacteria, though substantially less than cultures containing monocytes. No bacteria tested increased soluble IL-6 receptor release over spontaneous soluble IL-6 receptor release. We conclude that monocytes release IL-6 after contact with oral pathogens; however, soluble IL-6 receptor from T cells and monocytes is constitutively produced and may modulate IL-6 actions.